Legal Protection of Child As Victims of Crime of Rape - Arianus Harefa (Universitas Syiah Kuala, 2023)
Abstract: Along with the rapid flow of globalization and the negative impact of the development of information and communication technology is the occurrence of violence against children, especially related to sexual violence, which is increasing, where since the last year (2021) cases of violence against children have been reported reaching 11,952 cases, including 58,6 percent or 7,004 were cases of sexual violence. Based on this, the aim of this research is to identify and analyze forms of legal protection for children as victims of rape. This study uses a normative legal research type using approaches (1) statutory approach, (2) case approach, (3) conceptual approach, and also (4) analytic approach. (analitycal approach) with the data used, namely secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials, as well as qualitative analysis data using a descriptive, logical, and systematic approach so that they can answer problems or issues that exist and make withdrawals inductive to deductive conclusions. Based on the results of the research that legal protection for children as victims of the crime of rape in the Bandung District Court decision Number 989/Pid.Sus/ 2021/PN.Bdg and the Bandung High Court decision Number 86/Pid.Sus/2022/PT.Bdg on behalf of the defendant Herry Wirawan still has not provided protection to victims, especially in terms of providing compensation to victims in the form of compensation borne by the state and also fulfilling victims' rights in the form of recovery in the form of implementing both medical and social rehabilitation.